THE REVITALIZATION OF DELIBERATION VALUES IN THE EDUCATION OF DEMOCRACY IN INDONESIA: A STUDY OF SOEDIRMAN FIGURE VALUES - Sardiman Sardiman; Ajat Sudrajat; Djoko Suryo (Universitas Negeri Yogyakarta, 2017)
This research aims at analyzing the importance of deliberation values in developing democracy education in Indonesia. This research is a qualitative-historical research, i.e. reconstructing the expression and role of Soedirman struggle and his figure values, especially the value of deliberation. The values were then explored thoroughly using a sociological approach and some of the religious dimensions to get an idea of a more fundamental deliberation value as the principles of democratic development.The results show that Soedirman was successful becoming a leader both within the civil and military community and capable of upholding the values of the deliberation in performing his figure tasks. However, the deliberation values tend to be fading in this reformation era. Also, democracy is liberal and tends to be overly practiced. This should be improved by developing democracy education through the revitalization of deliberation values. The revitalization can be realized by performing dialogues and following deliberation traditions practiced by Soedirmanin order to strenghtenthe implementation of Pancasila-based democracy (Pancasila Democracy).Keywords: Figure values, deliberation, democracy.